Simulasi Antena Mikrostrip Patch Persegi Panjang Planar Array 6 Elemen Dengan Pencatuan Aperture Coupled Untuk Aplikasi CPE WiMAX Pada Frekuensi 3,3-3,4 GHz - Rezki Ananda Gusma; Yusnita Rahayu; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
WiMAX technology has high data transfer speed, large access range and mobility capability. To access the WiMAX network required Customer Premise Equipment (CPE). CPE require a little dimension antenna and integrated it easily. Therefore, microstrip antenna is a good candidate for this application. This paper, discuss design of 6 elements planar array rectangular microstrip patch antenna that can be used for CPE WiMAX application in 3.3 GHz (3.3-3.4 GHz). Microstrip antenna is designed using Aperture Coupled technique to improve the bandwidth. The design and simulation of microstrip antenna require Ansoft HFFS v.13. The simulation results show that antenna can operates in 3.3-3.4 GHz frequency. The value of the impedance bandwidth is 203.5 MHz (3.2405 to 3.444 GHz) or 6.09 % at VSWR ≤ 1.5 and gain is 7.4358 dBi. Keywords: CPE WiMAX, Planar Array, Aperture Coupled, VSWR, Gain.